Motivations behind managerial CSR decisions in European companies - A systematic literature review in the European context - Peitsara, Kristian (2025)
The concept of Corporate Social Responsibility (CSR) entered into the corporate vocabulary in the 1950s, but only became a more prominent concept in the 2000s. Corporate Social Responsibility (CSR) has slowly taken its place in mainstream management publications since the 1950s. Nevertheless, the research on motivations behind CSR decisions has been lacking behind, with CSR implementation and effectiveness having a more prominent focus in the academic literature.